Evaluation of long-read sequencing for Ostreid herpesvirus type 1 genome characterization from Magallana gigas infected tissues - Aurélie Dotto-Maurel; Camille Pelletier; Lionel Degremont; Serge Heurtebise; Isabelle Arzul; Benjamin Morga; Germain Chevignon (Microbiology Spectrum)
ABSTRACT Since the 1990s, the Pacific oyster Magallana gigas has faced significant mortality, which has been associated with the detection of the Ostreid Herpesvirus type 1 (OsHV-1). Due to the complex genomic architecture and the presence of multiple genomic isomers, short-read sequencing using Illumina method struggles to accurately assemble tandem and repeat regions and to identify and characterize large structural variations in the OsHV-1 genome. Third-generation sequencing technologies, as long-read real-time nanopore sequencing from Oxford Nanopore Technologies (ONT), offer new possibilities for OsHV-1 whole-genome analysis. Identification of the best method for extraction of high molecular weight (HMW) DNA and development of accurate bioinformatic pipelines for its characterization are now required. To this end, we evaluated and compared six HMW methods and one conventional DNA extraction kit for their ability to extract OsHV-1 DNA from M. gigas-infected tissues. We then evaluated the ability of ONT sequencing to produce an accurate OsHV-1 genome from both whole-genome and “adaptive sampling” (AS) sequencing approaches. Finally, we evaluated the efficiency of bioinformatics tools for de novo assembly and consensus calling to generate accurate OsHV-1 genomes. The HMW DNA extraction kit coupled with ONT sequencing and dedicated bioinformatics tools allowed us to produce accurate OsHV-1 genomes compared to those assembled using Illumina technology. The AS approach allowed up to 60% enrichment for viral data, and the long reads generated by ONT allowed the characterization of OsHV-1 isomers. Together with its portability, this sequencing shows great promise as a diagnostic tool for the characterization of unculturable aquatic viruses directly from host tissues.IMPORTANCEMany aquatic viruses threaten commercially valuable species and cause significant economic losses during outbreaks. To improve our understanding of the origin, transmission patterns and spread of these viruses, additional genomic data are essential. However, genomic characterization of unculturable large DNA viruses is a major challenge. In the present study, we have successfully evaluated the ability of ONT sequencing and adaptive sequencing (AS) to sequence and assemble the complete OsHV-1 genome. Our results show that it is now possible to sequence the whole genome of large DNA viruses directly from infected host tissue, without the need for prior in vitro propagation or prior laboratory steps for virus enrichment.